Crystallization Modalities in Polymer Melt Processing - Janeschitz-Kriegl, Hermann (Springer International Publishing, 2018)
In addition to structure formation in crystallizing polymers and semicrystalline polymers, this second edition completes the topic of transport phenomena. It also reviews solidification by crystallization during cooling and under flow or pressure, which all play an enormous role in polymer melt processing. Generally, there is an intensive interaction between three transport phenomena: heat transfer, momentum transfer (flow, rheology) and (flow induced) crystallization. The strong interaction between the three transport phenomena is a major challenge when it comes to experimentation, and advances in this area are detailed in the book, guiding further development of sound modeling. This book enables readers to follow an advanced course in polymer processing. It is a valuable resource for polymer chemists, applied physicists, rheologists, plastics engineers, mold makers and material scientists.